A cross-cultural adaptation and psychometric validation of SISRI-24 among Malaysian teachers - Ogunsola, Kazeem Olanrewaju; Fontaine, Rodrigue Ancelot Harvey; Jan, Muhammad Tahir (International Journal of Human Potentials Management, 2020)
The paper is aimed at validating the psychometric properties of SISRI-24 for effective performance among teachers in Malaysia. Through a list-based simple random sampling of 373 teachers, SISRI -24 was translated, adapted and validated. Using the TCA procedure, experts validated the translated instrument from both linguistic structure and semantic point of view. Its internal consistency was validated with Cronbach’s Alpha and CFA. EFA varimax normalized rotation extracted four components. The measure of internal consistency had Cronbach’s Alpha value of 0.911. CFA validated SISRI-19my with χ² / df ratio (354.512 / 141) = 2.514, RMSEA (0.077) and CFI (0.921) as reasonable spiritual intelligence fit model for Malaysian teachers. The adequacy of this paper’s findings is promising, suggesting that the Malaysian version of the spiritual Intelligence Self-Assessment Inventory scale would provide a valid instrument to measure spiritual intelligence among teachers. Practically, it would stimulate teaching interest irrespective of exigencies. Socially, it models spirited leaders whose role revolves on grooming younger generations towards nation-building. Psychologically, it acts as a catalyst for improved wellness. Theoretically, it contributes to the body of knowledge on spirituality and organizational behavior. Apart from the study is cross-sectional, it was limited only to private secondary school teachers. Future studies may include other strata of teachers to improve the SISRI-19my version. The study offers the first to empirically translate, adapt and validate a Malaysian version of SISRI-24.